2012
DOI: 10.1107/s1600536812051239
|View full text |Cite
|
Sign up to set email alerts
|

Cinnarizinium fumarate

Abstract: In the title salt {systematic name: 4-diphenyl­methyl-1-[(E)-3-phenyl­prop-2-en-1-yl]piperazin-1-ium (2Z)-3-carb­oxy­prop-2-enoate}, C26H29N2 +·C4H3O4 −, the piperazine ring in the cation adopts a distorted chair conformation and contains a positively charged N atom with quaternary character. The dihedral angle between the mean planes of the phenyl rings of the diphenyl­methyl group is 74.2 (7)° and those between these rings and the phenyl ring of the 3-phenyl­prop-2-en-1-yl group are 12.7 (9) and 80.6 (8)°. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…zepin-11-yl)piperazinium hemifumarate (Ravikumar & Sridhar, 2005), Cinnarizinium fumarate (Kavitha et al, 2013). In view of the importance of the incorporated of heterocyclic ring compounds and derivative of pyrimidyl piperazines, this paper reports the crystal structure of the title salt.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…zepin-11-yl)piperazinium hemifumarate (Ravikumar & Sridhar, 2005), Cinnarizinium fumarate (Kavitha et al, 2013). In view of the importance of the incorporated of heterocyclic ring compounds and derivative of pyrimidyl piperazines, this paper reports the crystal structure of the title salt.…”
Section: Methodsmentioning
confidence: 99%
“…For piperazine derivatives that have reached the stage of clinical application among the known drugs to treat anxiety, see: Tollefson et al (1991). For related structures, see: Betz et al (2011); Fun et al (2012); Jasinski et al (2010Jasinski et al ( , 2011; Kavitha et al (2013); Ravikumar & Sridhar (2005); Siddegowda et al (2011). For puckering parameters, see Cremer & Pople (1975).…”
Section: Related Literaturementioning
confidence: 99%
“…In spite of this, only the crystal structures of the neutral free-base molecule (Cheng et al, 2005;Sharma et al, 2015) and the salt ebastinium 3,5-dinitrobenzoate (Shaibah et al, 2017) have been reported to date. By contrast, fumarates (di-anion fumarate and mono-anion hydrogen fumarate) are common counter-anions in compounds of pharmacological importance; examples include opipramolium fumarate (Siddegowda et al, 2011), cinnarizinium fumarate (Kavitha et al, 2013) (technically, both hydrogen fumarates), and the recently reported structure of bis(4-acetoxy-N,N-dimethyltryptammonium)fumarate, a new crystalline form of psilacetin (Chadeayne et al, 2019). As part of our studies in this area, we now report the synthesis and crystal structure of the title 1:1 salt ebastinium hydrogen fumarate, C 32 H 40 NO 2 + ÁC 4 H 3 O 4 À , (I), formed in the reaction between ebastine and fumaric acid.…”
Section: Chemical Contextmentioning
confidence: 99%
“…Its pharmacodynamic and pharmacokinetic properties and its therapeutic use have been reviewed (Holmes et al, 1984). Brief reports on the structures of several salts derived from flunarizine Shivaprakash et al, 2014) and from substituted piperazine derivatives closely related to flunarizine Kavitha, Yildirim et al, 2013) have been published recently, and we report here the molecular and supramolecular structures of flunarizinium nicotinate, (I) (Fig. 1), and flunarizinediium bis(4-toluenesulfonate) dihydrate, (II) (Fig.…”
mentioning
confidence: 99%